2023
DOI: 10.3389/fphar.2023.1154377
|View full text |Cite
|
Sign up to set email alerts
|

Treatment discontinuation following low-dose TKIs in 248 chronic myeloid leukemia patients: Updated results from a campus CML real-life study

Abstract: TKIs long-term treatment in CML may lead to persistent adverse events (AEs) that can promote relevant morbidity and mortality. Consequently, TKIs dose reduction is often used to prevent AEs. However, data on its impact on successful treatment-free remission (TFR) are quite scarce. We conducted a retrospective study on the outcome of CML subjects who discontinued low-dose TKIs from 54 Italian hematology centers participating in the Campus CML network. Overall, 1.785 of 5.108 (35.0%) regularly followed CML patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Furthermore, it is imperative to ensure the administration of an adequate TKI dose to mitigate the emergence of resistant clones and achieve TFR. However, long-term TKI therapy may lead to chronic adverse events (AEs) that can significantly impact patients' quality of life and contribute to morbidity and mortality ( 11 ). Consequently, dose reductions due to AEs are a routine aspect of TKI management ( 12 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it is imperative to ensure the administration of an adequate TKI dose to mitigate the emergence of resistant clones and achieve TFR. However, long-term TKI therapy may lead to chronic adverse events (AEs) that can significantly impact patients' quality of life and contribute to morbidity and mortality ( 11 ). Consequently, dose reductions due to AEs are a routine aspect of TKI management ( 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, dose reductions due to AEs are a routine aspect of TKI management ( 12 ). Recent studies indicate that low-dose TKI therapy does not compromise the likelihood of attaining a DMR ( 11 , 13 ). However, the efficacy of low-dose TKI therapy is not extensively validated, and this approach is generally not recommended unless unavoidable, such as in cases of AEs.…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that a low dose of TKI before treatment discontinuation does not seem to hamper the probability of achieving a DMR and, thus, the probability of maintaining the TFR. 33 …”
Section: Alternative Strategies With Respect To Tki Discontinuationmentioning
confidence: 99%